Comparison of the Effectiveness of Compassion-Based Therapy and Mentalization-Based Interventions on Perceived Stress and Psychological Well-Being in Workers with Job Burnout - Mahmoudi Beram, Marzieh; Ghasemi Pirbalouti, Mohammad; Sharifi, Tayebeh (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to compare the effectiveness of a compassion-based intervention and a mentalization-based intervention on perceived stress and psychological well-being in workers experiencing job burnout. This study employed a quasi-experimental design with a pretest–posttest control group and a two-month follow-up. The statistical population included all workers with job burnout at Mansour Industry Factory in Falavarjan County in 2024. From this population, 60 participants were selected using purposive sampling and then randomly assigned to three groups of 20 participants each (two experimental groups and one control group). Data collection instruments included the Maslach Burnout Inventory (Maslach, 1981), the Perceived Stress Scale developed by Cohen and Kamarck (1983), and Ryff’s Psychological Well-Being Scale (Ryff, 1995). The first experimental group received mentalization-based training, and the second experimental group received a compassion-based intervention, each delivered in 12 sessions of 90 minutes, while the control group was placed on a waitlist. Data were analyzed using repeated-measures analysis of variance and Bonferroni post hoc tests. The results indicated that both interventions had a significant effect on perceived stress and psychological well-being, and the stability of these effects was maintained during the follow-up period (p < .05). Moreover, the findings showed that the compassion-based intervention was more effective than the mentalization-based intervention in reducing perceived stress and enhancing psychological well-being (p < .05). Accordingly, occupational and organizational counselors can utilize compassion-based and mentalization-based interventions to promote workers’ mental health and organizational performance.